Bio‐Engineered Fungal‐MOF Nanoplatform Synergizes Macrophage Polarization and Checkpoint Blockade for Potent Melanoma Immunotherapy - Xiaolong Li; Jueshuo Guo; Tingting Meng; Na Yu; Yaping Mai; Jianhong Yang; Wenbao Zuo (Advanced Healthcare Materials, 2026)
ABSTRACT The clinical efficacy of melanoma immunotherapy is frequently compromised by an immunosuppressive, “cold” tumor microenvironment (TME) driven by redox dysregulation and the metabolic polarization of tumor‐associated macrophages (TAMs). To overcome these intertwined barriers, a macrophage‐targeted, biomimetic nanoplatform (MOF‐808‐Ro‐G/N) is developed. This system integrates a catalytic metal–organic framework (MOF‐808) core loaded with a PERK inhibitor and a CD47 blocking agent, encapsulated within a Rhizopus oryzae (Ro)‐derived fungal shell. The biomimetic shell leverages Dectin‐1 interactions to enable precise TAM targeting and accumulation. Upon endocytosis, the acidic endosomal microenvironment activates the MOF core to deplete glutathione and trigger a surge of reactive oxygen species, thereby inducing immunogenic cell death. Synergistically, the released payloads disrupt the PERK‐ATF4 metabolic stress axis, reprogramming pro‐tumorigenic M2 TAMs toward an anti‐tumor M1 phenotype, while concurrently blocking the CD47‐SIRPα checkpoint to restore macrophage phagocytosis. Through this orchestrated modulation, MOF‐808‐Ro‐G/N effectively remodels the TME into an immunologically “hot” niche, promoting robust cytotoxic T lymphocyte infiltration and achieving substantial tumor growth suppression. Overall, this “metabolic–immune dual‐reprogramming” strategy provides a promising materials‐driven paradigm to overcome immunotherapy resistance in solid tumors.